If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 12 = 2x + 26 Reorder the terms: 12 + 3x = 2x + 26 Reorder the terms: 12 + 3x = 26 + 2x Solving 12 + 3x = 26 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 12 + 3x + -2x = 26 + 2x + -2x Combine like terms: 3x + -2x = 1x 12 + 1x = 26 + 2x + -2x Combine like terms: 2x + -2x = 0 12 + 1x = 26 + 0 12 + 1x = 26 Add '-12' to each side of the equation. 12 + -12 + 1x = 26 + -12 Combine like terms: 12 + -12 = 0 0 + 1x = 26 + -12 1x = 26 + -12 Combine like terms: 26 + -12 = 14 1x = 14 Divide each side by '1'. x = 14 Simplifying x = 14
| 2/k-6=28 | | 7(x+4)-3(x-5)=6 | | 42-3x=15 | | 1.3g+1.9=11.1 | | -3+5+-2= | | 4x+20=6x+2 | | -2+3x=-(6+x) | | 6x^3/5=162 | | -5=(1)(3)+b | | 3.9+3.8x=19.4+x | | 2(x-18)=74 | | -4(t-12)= | | 5x+-35=45 | | 43+-5= | | 11x-7=4x-35 | | 1=t-12 | | -5-8(1+7n)=-8n | | 184x+3=72-2 | | 1/2x-6=1/5x | | -77/-11= | | 5.9+7.3x=11.5+x | | -5=(-1)(3)+b | | -2p+(-1)(1-p)=-1p-4(1-p) | | 7/16x-1/8=1/6x | | b+-6= | | 11(g-7)= | | 2x^5-10x^4-18x^3=0 | | -3/7x=3/5 | | 12k^2-18k-12=0 | | 45-2/3x=67 | | 4/-10=5 | | -u/7=-23 |